Unequal ageing: the quality of life of senior citizens in the EU before and after COVID-19. A multidimensional approach - Roszko-Wójtowicz, Elżbieta; Przybysz, Klaudia; Stanimir, Agnieszka (Frontiers in Public Health, 2025)
IntroductionThe ageing population presents a significant demographic and socio-economic challenge for the European Union (EU). Declining fertility rates, coupled with increasing life expectancy, have led to a growing proportion of older individuals within the population, raising concerns about their quality of life. This study aims to assess the quality of life for seniors across EU countries in the years 2015, 2019, and 2022, with a particular focus on the impact of the COVID-19 pandemic. The research seeks to answer the following question: How has the quality of life among seniors in the EU evolved over time, and how has the COVID-19 pandemic affected this trajectory? We hypothesize that the pandemic has exacerbated existing socio-economic inequalities, particularly affecting the most vulnerable older populations.MethodsThis study utilises the Synthetic Measure of Senior Quality of Life (SMSQoL) to evaluate the living conditions of seniors across four critical domains: health, finances, social relations, and environment. Data for the analysis were drawn from Eurostat and national statistical reports, complemented by pilot studies conducted in selected EU countries. The pilot studies focused on gathering qualitative data to supplement the quantitative measures, especially in areas where standardised data were incomplete or unavailable. The assessment spans three years: 2015 (pre-pandemic baseline), 2019 (immediate pre-pandemic), and 2022 (post-pandemic). The analysis includes 27 EU member states and uses both descriptive and inferential statistical methods to evaluate trends and disparities. Cross-sectional analysis was applied to examine the impact of differing social policies, levels of social security, access to healthcare, and economic strength across these countries.ResultsThe analysis reveals significant disparities in the quality of life among seniors across EU countries, with pronounced differences between regions. In particular:Northern and Western Europe: seniors in these regions generally experienced improved overall life quality over the observed period. Countries such as Sweden and Germany reported gains in health, financial stability, and social relations, largely due to strong social policies and robust healthcare systems.Eastern Europe: Seniors in Eastern European countries, including Romania and Bulgaria, continued to face substantial challenges, with minimal improvements in quality of life. Economic instability, limited access to healthcare, and weaker social security systems were identified as key contributors to this stagnation.Impact of COVID-19: the pandemic exacerbated existing inequalities, particularly in the domains of social relations and finances. Seniors in economically vulnerable regions were disproportionately affected by social isolation and reduced income, intensifying the pre-existing challenges in their living conditions.Quantitative analysis confirmed that while some regions showed resilience, the most vulnerable populations experienced a sharp decline in their overall quality of life, particularly between 2019 and 2022.DiscussionThe findings from this study highlight the persistence of economic and social inequalities in the life conditions among seniors across the EU. While countries in Northern and Western Europe have made strides in improving senior living conditions, Eastern Europe continues to face significant challenges. The COVID-19 pandemic acted as a catalyst, exacerbating these inequalities, particularly in terms of social isolation and financial insecurity. These results align with previous studies that have highlighted the uneven impact of social policies and economic strength on senior well-being across Europe. The disparities underscore the need for more balanced and equitable policy interventions that can address the vulnerabilities of older populations, particularly in regions struggling with economic instability. Future research should focus on longitudinal studies that track the recovery trajectories of seniors post-pandemic and assess the effectiveness of policy measures aimed at mitigating these disparities.